2019
DOI: 10.7169/facm/1749
|View full text |Cite
|
Sign up to set email alerts
|

The Champernowne constant is not Poissonian

Abstract: We say that a sequence (xn) n∈N in [0, 1) has Poissonian pair correlations iffor every s ≥ 0. In this note we study the pair correlation statistics for the sequence of shifts of α, xn = {2 n α}, n = 1, 2, 3, . . ., where we choose α as the Champernowne constant in base 2. Throughout this article {·} denotes the fractional part of a real number. It is well known that (xn) n∈N has Poissonian pair correlations for almost all normal numbers α (in the sense of Lebesgue), but we will show that it does not have this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Therefore, if we study the distribution of the spacings between the sequence elements of ({b n α}) n∈N , the only reasonable choice for α is a b-normal number. In [23], the sequence ({2 n α}) n∈N was studied for the Champernowne constant α and it was shown that it is not Poissonian. In this note we will choose two other special instances, which were suggested by Yann Bugeaud as potential candidates in personal communication.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…Therefore, if we study the distribution of the spacings between the sequence elements of ({b n α}) n∈N , the only reasonable choice for α is a b-normal number. In [23], the sequence ({2 n α}) n∈N was studied for the Champernowne constant α and it was shown that it is not Poissonian. In this note we will choose two other special instances, which were suggested by Yann Bugeaud as potential candidates in personal communication.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…Since low-discrepancy sequences may be interpreted as sequences which are as uniformly distributed as possible, there might be examples of sequences in this class having Poissonian pair correlations. However, all attempts to find such examples have failed so far and it has even been proved for many explicit types of low-discrepancy sequences (in dimension d = 1 and also in higher dimensions) that they do not have Poissonian pair correlations, see [4,15,23,32]. In this article, we will argue why it might nonetheless be worth to keep on looking for examples of Poissonian pair correlations in the class of low-discrepancy sequences.…”
Section: Introductionmentioning
confidence: 93%
“…The only known positive result is (x n ) = { √ n}, see [2], where {z} := z − ⌊z⌋ denotes the fractional part of z. Indeed, many canonical candidates of uniformly distributed sequences are known to fail having Poissonian pair correlations, see [3], [5], [10]. In this paper, we work with a definition that allows us to measure how far a sequence is from having Poissonian pair correlations.…”
Section: Introductionmentioning
confidence: 99%